1996
DOI: 10.1123/ijsn.6.3.213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Creatine Monohydrate Supplementation on Running Velocity

Abstract: Creatine supplementation has been shown to augment muscle PCr content and increase the rate of ATP resynthesis. Thus, we hypothesized that creatine supplementation might enhance sprinting performance. Eighteen subjects completed both of two testingsessions(control and postsupplement) 1 week apart, wherein they sprinted three 60-m distancetrialsthat were recorded with videotape. Following the control session, for 7 days, subjects in the treatmentgroupingested a creatine-glucose mixture, while the placebogroupco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Redondo, Dowling, Graham, Almada, Williams (1996) found that with ice hockey and soccer players, statistically significant differences were not found in 3 × 60 m sprints with 2 minute resting breaks between the sprints. The reason for the differences among the study results might be the variability in the number of repeated sprint times or possible influences of energy sources.…”
Section: Discussionmentioning
confidence: 92%
“…Redondo, Dowling, Graham, Almada, Williams (1996) found that with ice hockey and soccer players, statistically significant differences were not found in 3 × 60 m sprints with 2 minute resting breaks between the sprints. The reason for the differences among the study results might be the variability in the number of repeated sprint times or possible influences of energy sources.…”
Section: Discussionmentioning
confidence: 92%
“…Many studies did not observe any particular ergogenic effect of exogenous Cr on performance during single sprint protocols [1,[11][12][13]. We anticipated that exogenous Cr would be ergogenic for anaerobic exercise mainly when the effect of fatigue appears.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reports suggest that Cr supplementation enhances exercise performance (Balsom et al 1993;Greenhaff et al 1993Greenhaff et al , 1994Birch et al 1994;Earnest et al 1995;Prevost et al 1997;Maganaris & Maughan, 1998), although a number of studies have shown no effect (Febbraio et al 1995;Redondo et al 1996;Vandenberghe et al 1996). In part, it seems the disparity in the findings occurs because of differences in the exercise model employed, or the intensity, duration, and frequency of the task, and the level of fitness of the subjects.…”
mentioning
confidence: 60%